The Essential Guide to the Loch Ness Monster and Other Aquatic Cryptids by Ken Gerhard - Bauer, Henry (Journal of Scientific Exploration, 2022)
This is a readable overview of reports of unidentified aquatic creatures in the oceans and in freshwater, and it can be a useful introduction for people who have not previously read much about this subject. Cryptozoologists, however, will find nothing new here; the treatment is purely descriptive rather than analytical and critical. A nice Foreword by Steve Feltham, in residence at Loch Ness for 30 years looking for Nessies, includes the important point that the number of actual sightings is a large multiple of the number of publicly known reports. The first two chapters are about the Loch Ness Monster. Chapter 3 deals with sea serpents. Chapters 4 through 6 are about the Canadian “Ogopogo” of Lake Okanogan, the American “Champ” of Lake Champlain, and less-well-known lake monsters of North America. Chapter 7 reports on lake monsters around the world. Chapter 8 surveys the typically mysterious carcasses periodically found on seashores. Chapter 9 mentions the surprises that the ocean depths occasionally reveal, notably the coelacanth, the giant squid, and the megamouth shark, as well as the little-known beaked whales, oarfish, and sturgeon of monstrous size.